Pendekatan Restoratif Sebagai Alternatif Sanksi Pidana Dalam Kejahatan Korporasi - Mirsa Astuti; Muhammad Faris Aksa (Iuris Studia: Jurnal Kajian Hukum, 2021)
A corporation is a body consisting of a group of people and its members have their respective rights and obligations, which are separate from the rights and obligations of each member. Corporations have deviant behavior and high authority in a corporation and use their position as a tool to violate the law, so it is often also called economic crime as a corporate crime. In tackling and eradicating corporate crime, Indonesia as a state of law provides a way out in resolving various corporate criminal cases in a more responsible manner. Eradication of corporate crime in Indonesia initially emphasized a repressive and preventive approach, but in its development several changes were seen, namely using a repressive and preventive approach together, both in material and formal criminal law provisions. This study uses library research methods or library research. The data source used is secondary data by processing data from primary legal materials, secondary legal materials and tertiary legal materials